2017
DOI: 10.4081/ejtm.2017.6488
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrical stimulation on motor nerve regeneration in sciatic nerve ligated-mice

Abstract: The purpose of this study was to investigate the effect of electrical stimulation on sciatic nerve regeneration and functional recovery of target muscles. Mice were randomly divided into 3 groups: ligated without electrical stimulation, ligated with electrical stimulation and control (non-ligated). The unilateral peripheral mononeuropathy was produced on the right hind limb. Sciatic nerve was then electrically stimulated daily for a period of 2 weeks (duration: 0.2 msec, frequency: 100Hz, amplitude: 15mA). Evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Excess current can damage the nerve and surrounding tissue, but this can be mediated by altering the frequency of stimulation [73]. Frequencies ranging from 5 -200 Hz have been used for RES, similar to those reported for neuromodulation and FES, suggesting that FES and neuromodulation could be having the unintended effect of upregulating neuroregenerative genes [9,11,60,65,74]. Twenty Hz, which is most widely used in RES experiments, was first selected because it is the mean spontaneous frequency of motoneuron firing, but other frequencies can have therapeutic benefits [60].…”
Section: Electrical Stimulation Parametersmentioning
confidence: 72%
See 1 more Smart Citation
“…Excess current can damage the nerve and surrounding tissue, but this can be mediated by altering the frequency of stimulation [73]. Frequencies ranging from 5 -200 Hz have been used for RES, similar to those reported for neuromodulation and FES, suggesting that FES and neuromodulation could be having the unintended effect of upregulating neuroregenerative genes [9,11,60,65,74]. Twenty Hz, which is most widely used in RES experiments, was first selected because it is the mean spontaneous frequency of motoneuron firing, but other frequencies can have therapeutic benefits [60].…”
Section: Electrical Stimulation Parametersmentioning
confidence: 72%
“…RES, in contrast, promotes nerve sprouting, neuroregeneration, reinnervation of target organs, and functional recovery after nerve injury [9][10][11][12][13][14]. RES upregulates brain derived neurotrophic factor (BDNF) in motoneurons, which in turn upregulates regeneration associated genes, providing possibilities for therapy of neurogenic lower urinary tract dysfunction due to peripheral or central nerve injury, as well as other urological conditions that can result from nerve injury, such as erectile dysfunction, neurogenic bladder, and underactive bladder [15].…”
Section: Introductionmentioning
confidence: 99%
“…This finding shows that multiple stimulations with various durations and frequencies, as well as harvesting the tissue on different days, may elicit significant results. An animal study by Samiee et al 18 showed that the electrical stimulation in the sciatic nerve accelerated nerve repair and indirectly improved biceps femoris muscle force to a comparable level with control without effecting muscle sensitivity. In that study, the rat's sciatic nerve was subjected to daily electrical stimulation for 2 weeks (duration: 0.2 sec, frequency: 100 Hz, amplitude: 15 mA).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that M2 macrophages regulate the inflammatory response in Wallerian degeneration, and the regeneration of nerves can occur in parallel or alternately. 18 Sprouting axons originate in the terminal nodes of Ranvier, formed shortly after peripheral nerve trauma and extended to the surface of the Schwann cells or the interior of the basal lamina. When the proximal and distal stumps coincide, the growth and branching of axons can provide a framework for nerve fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Nerve stimulation depends on various parameters. [ 21 ] In other words, it is possible that changing the frequency and amplitude of the stimulation signal to the muscle changes the EMG signal, or changing the frequency and amplitude of the stimulation signal to the muscle can change the angle of the joint. [ 22 ] Most of the proposed biological models based on external stimulation to the hand muscles that were previously designed using nonlinear systems and mathematics, including chaotic equations (which are the most similar ones to the biological system), have not been used in this study, and therefore, a new stimulation model derived from the Rossler chaotic equation is specifically utilized to create nonlinear conditions in the muscle.…”
Section: Introductionmentioning
confidence: 99%